THE USE OF CODE MIXING ON INSTAGRAM BY THE STUDENTS OF ENGLISH LANGUAGE EDUCATION - Hilda, Livia; Ramendra, Dewa Putu; Mahendrayana, Gede (Universitas Pendidikan Ganesha, 2020)
This study aimed at analyzing the use of code mixing on Instagram by the students of English Language Education Department which covered the types and the reasons of using code mixing. The design of this study was descriptive qualitative study which only focused on describing Indonesian-English code mixing used by ELE students. The participants of this study were the fourth semester students of English Language Education Department at Ganesha University of Education. The data were collected by observing the participants’ Instagram account and interviewing the participants through Google Form. The data were analyzed using the combination of some theories. Hoffman, Ho, and Muysken’s theories were combined and used to analyze the types of code mixing. Meanwhile, to analyze the reason of using code mixing, Hocket, Hoffman, and Saville-Troike’s theories were used. The result showed that most of the participants used intra-sentential type of code mixing with 107 occurrences (56%) from the total of 191 data. The result also showed that need filling motive was the reason mostly chosen by 21 (43,8%) out of 48 participants.